Patchiness of plankton ecosystem structure due to nutrient mixing along the shelf edge in the North Sea - Axelle Cordier; Jørgen Bendtsen; Niels Daugbjerg; Nikolaj From; Sigrún Huld Jónasdóttir; Erik Askov Mousing; Jens Tang Christensen; Teresa Silva; Katherine Richardson (Scientific Reports)
Abstract Mid-water column turbulence has been shown to cause elevated vertical nutrient flux at the shelf edge in the northeastern North Sea. Here, we demonstrate that phytoplankton communities in this region tend to be dominated by larger cells (estimated from percentage of chlorophyll captured on a 10 μm filter) than beyond the shelf edge. Fv/Fm (PSII electron transport capacity) corrected for photoinhibition in the surface layer correlated in this study with the percentage of chlorophyll captured on a 10 µm filter (assumed to be large cells), suggesting that the phytoplankton community was responding to increased nutrients in the euphotic zone by increasing photosynthetic efficiency and altering community composition. The greatest abundances of larger copepods and the highest rates of Centropages typicus egg production were also generally found at the shelf edge. These results suggested that impact from increased nutrient fluxes cascaded up the planktonic food web. As these regions of nutrient flux were very localised, this led to sub-mesoscale heterogeneity in plankton ecosystem structure. Reports of higher abundances of fish and mammals at the shelf edge are common and we hypothesise that their distributions are a response to the impact of mid-water column nutrient upwelling on the plankton food web in the region.